Temporary employment, job flows and productivity: A tale of two reforms - Lorenzo Cappellari; Carlo Dell'Aringa; Marco Leonardi (Institute for the Study of Labor (IZA), 2012)
We investigate the effects of two reforms of temporary employment using panel data on Italian firms. We exploit variation in their implementation across regions and sectors for identification. Our results show that the reform of apprenticeship contracts increased job turnover and induced the substitution of external staff with firms' apprentices, with an overall productivity-enhancing effect. The reform of fixed-term contracts instead did not produce the intended results: it induced a substitution of temporary employees in favour of external staff and reduced capital intensity, generating productivity losses. We estimate substitution elasticities across various types of temporary contracts that are consistent with this interpretation.
urn:nbn:de:101:1-2012081412516
Keywords: J24; J41; 330; employment contracts; productivity; institutional changes; Befristeter Arbeitsvertrag; Reform; Wirkungsanalyse; Arbeitsnachfrage; Arbeitsmobilität; Produktivität; Arbeitsverhältnis; Substitutionselastizität; Schätzung; Italien